A phase 2 multicentre study of siltuximab, an anti‐interleukin‐6 monoclonal antibody, in patients with relapsed or refractory multiple myeloma. (25th February 2013) - Voorhees, Peter M.; Manges, Robert F.; Sonneveld, Pieter; Jagannath, Sundar; Somlo, George; Krishnan, Amrita; Lentzsch, Suzanne; Frank, Richard C.; Zweegman, Sonja; Wijermans, Pierre W.; Orlowski, Robert Z.; Kranenburg, Britte; et al.
Summary Interleukin‐6 (IL6) plays a central role in multiple myeloma pathogenesis and confers resistance to corticosteroid‐induced apoptosis. We therefore evaluated the efficacy and safety of siltuximab, an anti‐IL6 monoclonal antibody, alone and in combination with dexamethasone, for patients with relapsed or refractory multiple myeloma who had ≥2 prior lines of therapy, one of which had to be bortezomib‐based. Fourteen initial patients received siltuximab alone, 10 of whom had dexamethasone added for suboptimal response; 39 subsequent patients were treated with concurrent siltuximab and dexamethasone. Patients received a median of four prior lines of therapy, 83% were relapsed and refractory, and 70% refractory to their last dexamethasone‐containing regimen. Suppression of serum C‐reactive protein levels, a surrogate marker of IL6 inhibition, was demonstrated. There were no responses to siltuximab but combination therapy yielded a partial (17%) + minimal (6%) response rate of 23%, with responses seen in dexamethasone‐refractory disease. The median time to progression, progression‐free survival and overall survival for combination therapy was 4·4, 3·7 and 20·4 months respectively. Haematological toxicity was common but manageable. Infections occurred in 57% of combination‐treated patients, including ≥grade 3 infections in 18%. Further study of siltuximab in modern corticosteroid‐containing myeloma regimens is warranted, with special attention to infection‐related toxicity.